Avaliação da qualidade da silagem de milho pós-cultivo de pastagens de inverno - Tubin, Jéssica (2015)
Corn is the most traditionally used by farmers feed and to present optimal conditions for producing good silage, taking into account that the quality of silage, and the nutritional requirements of the plant are determined by the amount of nutrients to the plant extracts during its cycle. The experiment was conducted in the Cidade de Dois Vizinhos and the objective was to evaluate the quality and the production of corn silage post cultivation of winter pastures, in a livestock farming system integration. The experimental area was used 7 acres where corn was sown Agroeste 1572 PRO. The harvest of corn silage occurred when the grains reach the dough stage represented by marking the milk line delimiting two thirds of the grain which corresponds to an ideal dry matter content ranging from 32% to 35%. The silage was stored in micro-silos made of PVC tubes with sealing the ends and these remained closed for 60 days for fermentation to occur of good quality. The experimental design was a randomized block design, consisting of three blocks and are subdivided into 5 treatments and 3 replications, as follows; T1 = sown maize after oat + ryegrass grazing + supplement, T2 = corn sown after grazing oat + ryegrass + vetch, T3 = sown maize after oat grazing ryegrass + vetch supplement, and T4 = sown maize after oat grazing + ryegrass + supplement without grazing, T5 = sown maize after oat grazing ryegrass + + vetch without grazing. The results showed no significant differences between treatments, and only crude protein differed from the other. The production of corn silage was not affected by grazing which preceded the corn, and the PB increased livestock integrated crop areas using the vetch with oat and ryegrass pasture.